IMPLEMENTASI STANDAR SARPRAS MENURUT PERMENDIKNAS NOMOR 40 TAHUN 2008 DI SMK DARUSSALAM - Nur Hidayati; Indah Fajri Safitri (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
Education is knowledge that every student must have. And educational institutions are required to have sarpras as stated in the minister of National Education Regulation No. 40 of 2008 concerning the sarpras standards for vocational high schools to support learning. The discussinon in this study is how the complementation of sarpras in SMK Darussalam according to Permendiknas No. 40 of 2008. This study uses a qualitative descriptive method with data analysis techniques, reduction processes, data colleection, data presentation, and conclusion drawing. The methods used: Observation, Interview, Documentation. Research subjects: principal, WK. Sarpras, computer network engineering staff, and TU staff. The author concludes that the completeness and feasibility of sarpras in SMK Darussalam is in accordance with the Minister of National Education Regulation no. 40 of 2008 which includes land, building, and infrastructure atandards. As well as the implementation of sarpras in SMK Darussalam in accordance with the minister of National Education No. 40 OF 2008 covering the capacity of students, land area, completeness of practice rooms, special equipment, and general equipment.